The development of a facial animation system based on performance and the use of an RGB-D camera - Da Silva, Carlos Eduardo Rossi Cubas [UNESP]; Sementille, Antonio Carlos [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2017)
In recent decades, interest in capturing human face movements and identifying expressions for the purpose of generating realistic facial animations has increased in both the scientific community and the entertainment industry. We present a modular framework for testing algorithms used in performance-based facial animation. The framework includes the modules used in pipelines found in the literature as a module for creating datasets of blendshapes, an algorithm processing module for identification of weights and, finally, a redirection module that creates a virtual face based on blendshapes. The framework uses a RGB-D camera, the RealSense F200 camera from Intel. The entire framework is based on blendshapes that are blends of shapes.
Keywords: Blendshapes; Capture facial movements; Retargeting